Association Between Left Ventricle Ejection Fraction and Vitamin D Levels in Congestive Heart Failure; A Cross Sectional Study - Betul Ozdemir (Research Center for Rational Use of Drugs (RCRUD), 2020)
Objective: Congestive heart failure (HF) is a chronic disease that incidence is growing in the population. Vitamin D effects on directly myocardial cells. The aim of this study was to investigate the association between vitamin D levels with ejection fraction of left vetricule. Methods: The study population consisted of 101 patients admitted with heart failure. Age, gender, and demographic characteristics (diabetes mellitus, hypertension, smoking-nonsmoking, coronary artery disease) of all patients were recorded. In all patients for blood analyses vitamin D, creatine, crp and lipid profile were studied. And all patients were studied echocardiography. Results: HF patients, in our population 35 (34.7%) patient is female and 66 (65.3%) patient is male. The mean age of our patients was calculated as 67.4± 12.9 years. Our patients laboratory parameters mean were measured for vitamin D 24.3±17.3 ng/ml. LVEF mean was measured 31.8±9.5. In our study group LVEF and vitamin D was correlated with each other Conclusions: Vitamin D and LVEF had a positive correlation in heart failure patients. It may be occured with the protective effect of vitamin D or consequence of hipovitaminosis.